Social Support Celebrity Worship and Well Being in JKT48 Fans: Dukungan Sosial, Pengkultusan Selebriti, dan Kesejahteraan di Kalangan Penggemar JKT48 - Nandito Dwi Prasetyo; Lely Ika Mariyati (Academia Open, 2025)
General Background Subjective well-being is a central construct in psychology that reflects individuals’ evaluations of life satisfaction and emotional experiences, particularly within social and cultural contexts such as fandom communities. Specific Background Fans of idol groups often form strong emotional attachments and social networks that may shape their psychological functioning, including perceived happiness and life satisfaction. Knowledge Gap Despite extensive research on well-being across populations, limited empirical attention has been directed toward idol fandom communities, particularly JKT48 fans in regional contexts. Aims This study examines the relationship between social support and celebrity worship with subjective well-being among members of the JKT48 fan community in Sidoarjo using a quantitative correlational design. Results Findings from multiple linear regression indicate that social support and celebrity worship each show positive and significant associations with subjective well-being, both individually and jointly, accounting for 23.8% of variance. Additionally, male fans exhibit higher levels of celebrity worship than female fans. Novelty The study contributes new empirical evidence by focusing specifically on a regional idol fandom community that has not previously been examined in relation to subjective well-being. Implications These results suggest that adaptive engagement in fandom, supported by interpersonal connections, is linked to favorable psychological outcomes, highlighting the importance of balanced parasocial attachment and community support for mental health within fan cultures. Highlights: Interpersonal backing within the fan community is positively associated with life satisfaction and emotional states. Strong attachment to idols corresponds with higher psychological appraisal scores among participants. Male participants demonstrate greater levels of idol fixation compared with female participants. Keywords: Subjective Well-Being; Social Support; Celebrity Worship; Fandom Psychology; JKT48 Fans